Penerapan Strategi Belajar Self-Talk Instruksional terhadap Hasil Belajar Keterampilan Dasar Defensive Clear dan Long Service pada Permainan Bulutangkis - Riansyah, Riansyah; Hidayat, Yusuf; Septian, Regi Dwi; Abdullah Al Ghazali, Muhamad Dzikry; Hambali, Burhan; Nugraha, Reshandi; Satria, Muhammad (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
The aim is to test the effect of instructional self-talk learning strategies on basic defensive clear and long service skills. The research was carried out using the experimental method on 32 Pinggir Sari 1 elementary school students consisting of 16 experimental group students and 16 control group students, which was carried out using a technique (random sampling). The results of the calculation of the independent samples t-test data for the experimental group and the defensive clear control group use the assumption of equal variances, which is seen from the average value of the experimental group, which is higher than the control group, namely (20.93 > 7.31) and the results of the test calculations independent samples t-test data for the experimental group and the extended service control group using the assumption of equal variances not assumed which is seen from the average value of the experimental group which is higher than the control group, namely (18.50 > 7.93). Conclusion: The instructional self-talk learning strategy significantly influences overall learning outcomes for basic skills. Keywords: Defensive precise, Instructional self-talk, Long service